The Freedom of a Teenager: Vocation and Service Learning as the Future of Youth Ministry - Myers, Jeremy (Dialog, 2008)
This article asserts the value of service learning as integral to youth ministry's future. However, service learning often lacks an appropriate philosophical foundation and an effectual process. Therefore, we offer Luther's doctrine of vocation as a framework for engaging youth in service experiences, which in return becomes a concrete way to experience the doctrine of vocation and, more importantly, the freedom of a Christian. Framed and interpreted through a vocational lens, service experiences aid youth in recognizing the urgency of a life of faith,